1982
DOI: 10.1093/bja/54.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Four Narcotic Analgesics for Extradural Analgesia

Abstract: The effectiveness of extradural injections of morphine sulphate 6 mg, methadone 6 mg, pethidine 60 mg and fentanyl 60 micrograms in relieving pain after operation were compared in 24 patients. The average duration of pain relief following morphine was 12.3 h; methadone 8.7 h, pethidine 6.6 h and fentanyl 5.7 h. There was no significant difference in the efficacy of the four drugs. There were no effects of clinical importance on heart rate, respiratory frequency or arterial pressure, but arterial systolic press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

1986
1986
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(18 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…It is anticipated that if no patients had been electively catheterised this difference would have been even greater. Previous studies have also shown a high incidence of catheterisation with epidural morphine ranging from 10% (retrospective) to 100% [2,3,12,15,18,20,30,31,52,53] and again this appears to be dose dependent. A retrospective study of 2000 women receiving epidural pethidine failed to demonstrate any evidence of urinary retention [37].…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…It is anticipated that if no patients had been electively catheterised this difference would have been even greater. Previous studies have also shown a high incidence of catheterisation with epidural morphine ranging from 10% (retrospective) to 100% [2,3,12,15,18,20,30,31,52,53] and again this appears to be dose dependent. A retrospective study of 2000 women receiving epidural pethidine failed to demonstrate any evidence of urinary retention [37].…”
Section: Discussionmentioning
confidence: 72%
“…Most studies have given an opioid bolus and assessed the analgesic effect and the duration of action [3,4,7,9,14,[16][17][18][19][20][21][22][23]. From these data we calculated approximately equipotent 24-h dosages for each drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mechanism of respiratory depression after epidural morphine seems to be related to morphine's low lipid solubility. In comparison with hydrophilic drugs, the rapid uptake of extradural lipophilic compounds reduces their capacity to cause late respiratory depression 20 .…”
Section: Discussionmentioning
confidence: 99%